Transfer Pricing, Thin Capitalization, and Intangible Assets' Impact on Tax Avoidance: Evidence from Indonesian Manufacturing Firms (2022-2024) - Disya Yuke Farhana; Enggar Diah Puspa Arum; Ilham Wahyudi; Wiralestari Wiralestari (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2026)
This study examines the effect of transfer pricing, thin capitalization, and intangible assets on tax avoidance among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2022-2024. Using a purposive sampling method, 90 firms were selected, yielding 262 firm-year observations after removing 8 outliers from an initial pool of 270. Tax avoidance is proxied by the Cash Effective Tax Rate (CETR); transfer pricing by the Related Party Transaction ratio (RPT); thin capitalization by the Debt-to-Equity Ratio (DER); and intangible assets by the ratio of intangible assets to total assets. The results indicate that transfer pricing has a significant negative effect on tax avoidance, thin capitalization has a significant negative effect on tax avoidance, and intangible assets do not significantly affect tax avoidance. The model is jointly significant (F = 25.422; p < .001) with an Adjusted R² of 21.92%, indicating that 21.92% of the variation in tax avoidance is explained by the three independent variables. These findings carry important implications for tax authorities seeking to strengthen oversight of related-party transactions and the capital structures of multinational enterprises.